Analysis Of The Effect Of The Speed Of THE cnc Router Spindle On The Surface Roughness Of The Workpiece - Muhammad Lyan Syaputra (Universitas Riau Kepulauan, 2024)
In the machining process, the speed grip of the CNC Router spindle on the surface area of the activity entity is very closely monitored and the physical quality of the cutting surface is also on the amount of cutting speed, thickness of the tape and the strength of the film. The aim of the study is to understand the speed grip of the CNC Router on the surface mill system on the surface surface of the activity entity. using spindle speeds of 1000 rpm, 1200 rpm and 1400 rpm. The equipment and materials in this study are aluminum and measuring equipment. Based on the results of the visual study, it was found that the largest and most aggressive flat body was seen at a spindle speed of 1000 rpm, and a stable flat body was seen at a spindle speed of 1200 rpm, then the smallest or strongest flat body was seen at a speed of 1400 rpm while the data from studies using Roughness Tests, it shows that the average Ra point at a spindle speed of 1000 rpm is 0.33 um, at a spindle speed of 1200 the Ra point is 0.30 µm, and at a spindle speed of 1400 rpm the Ra is 0.29 µm. From the results of the study, it was found that the smaller and higher the spindle rotation, the grip on the physical surface on the face mill of the experimental entity and the higher the speed of the spindle, the smoother the surface, and vice versa, the smaller the spindle rotation, the more aggressive the surface. Keywords: Spindle Speed and Surface Roughness.